Systematic review of psychiatric signs in Niemann-Pick disease type C. (21st April 2019) - Bonnot, Olivier; Klünemann, Hans-Hermann; Velten, Christian; Torres Martin, Juan Vicente; Walterfang, Mark
Abstract: Objectives: We conducted the first systematic literature review and analysis of psychiatric manifestations in Niemann-Pick disease type C (NPC) to describe: (1) time of occurrence of psychiatric manifestations relative to other disease manifestations; and (2) frequent combinations of psychiatric, neurological and visceral disease manifestations. Methods: A systematic EMBase literature search was conducted to identify, collate and analyze published data from patients with NPC associated with psychiatric symptoms, published between January 1967 and November 2015. Results: Of 152 identified publications 40 were included after screening that contained useable data from 58 NPC patients (mean [SD] age at diagnosis of NPC 27.8 [15.1] years). Among patients with available data, cognitive, memory and instrumental impairments were most frequent (90% of patients), followed by psychosis (62%), altered behavior (52%) and mood disorders (38%). Psychiatric manifestations were reported before or at neurological disease onset in 41 (76%) patients; organic signs (e.g., hepatosplenomegaly, hearing problems) were reported before psychiatric manifestations in 12 (22%). Substantial delays to diagnosis were observed (5–6 years between psychiatric presentation and NPC diagnosis). Conclusions: NPC should be considered as a possible cause of psychiatric manifestations in patients with an atypical disease course, acute-onset psychosis, treatment failure, and/or certain combinations of psychiatric/neurological/visceral symptoms.